Peningkatan Kesadaran Perilaku Hidup Bersih dan Sehat di Pondok Pesantren Abnaul Amir Kabupaten Gowa: Increasing Awareness of Clean and Healthy Living Behavior at the Abnaul Amir Islamic Boarding School, Gowa Regency - Arranury, Zil Fadhilah; Wijaya, Dian Rezki; Yusmaniar, Wilda; Bahsur, Muh Nur Ichsan (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Islamic boarding schools, as Islamic educational institutions in Indonesia, are important in supporting health programs, especially in promoting health and cleanliness in everyday life. This service aims to increase the knowledge and awareness of Islamic boarding school students about PHBS. The service uses the SL (Service Learning) approach through counseling on Clean and Healthy Living Behavior at the Abnaul Amir Islamic boarding school, Kab. Gowa. The results of this service activity show a positive response from Islamic boarding school students, as seen from their activeness during counseling and increased understanding regarding PHBS after the counseling. Abnaul Amir Islamic boarding school students have a good understanding of PHBS, so they are expected to be able to keep themselves and their environment clean and healthy independently.